The effect of enhanced recovery after surgery combined with fine surgical nursing on rehabilitation after lung cancer surgery - Dong, Jiali; Zhu, Xiaoling (Journal of the Pakistan Medical Association, 2024)
Objective: To analyse the enhanced recovery after surgery approach combined with fine surgical nursing on recovery time, pain, sleep quality and satisfaction with care after lung cancer surgery. Method: The cross-sectional study was conducted at the Nanjing Chest Hospital, China, from October 2019 to March 2022, and comprised non-small cell lung cancer patients undergoing single-port video-assisted thoracoscopic surgery. Patients receiving fine surgical nursing in addition to conventional enhanced recovery after surgery formed the intervention group A, while those receiving the conventional enhanced recovery after surgery care alone formed control group B. Intraoperative blood loss, operative time, extubation time and length of stay values for noted for both the groups using standard scales. Nursing satisfaction and the incidence of adverse reactions in the two groups were also noted. Data was analysed using SPSS 23. Results: Of the 99 patients, 46(46.5%) were in group A; 23(50%) males and 23(50%) females with mean age 70.3±4.8 years and mean body mass index 26.76±2.55kg/m2. There were 53(53.5%) patients in group B: 16(30.2%) males and 37(69.8%) females with mean age 69.9±4.4 years and mean body mass index 25.93±2.40kg/m2 (p>0.05). Intraoperative blood loss, operative time, postoperative extubation time and length of stay in group A were lower than those in group B (p<0.05). Pain and sleep quality values in group A were lower, while health status value was higher than group B (p<0.05). Group A had significantly higher nursing satisfaction compared to group B (p<0.05). Conclusion: The use of enhanced recovery after surgery combined with fine surgical nursing in patients with non-small cell lung cancer after video-assisted thoracoscopic surgery promoted postoperative recovery. Key Word: Enhanced recovery after surgery, Thoracic surgery, Video-assisted, Non-small cell lung cancer, Visual analogue scale, Perioperative nursing.